MANGROVE AND ITS EFFECT ON THE DEVELOPMENT OF SMALL RUMINANTS IN THE COASTAL AREAS - Didiek Rahmadi (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Mangrove has as an important role in the coastal area. Thus, it must be managed properly. An experiment on its management was carried out in Morodemak villages, Bonang subdistrict, Demak district, central Java Province. Sheep owned by the fisherman were used as a material of the experiment. These were taking using purposive random sampling method. Sample was chosen from three different locations. It was determined on the basis of the distance from farmer housing to the mangrove areas. It was divided into three categories, namely: close: 0-2 km; medium: 2-4 km; and distant: >4 km). survey was done in order to collect data on mangrove, management system, and status of hematology (triglyceride and protein total of plasma blood) of sheep. The experiment was conducted by managing the sheep traditionally by giving them indigenous grass and leaf mangrove. There was no difference in the content of triglyceride and protein total of plasma blood of sheep managed at three different areas. This phenomenon occurred due to only the quality of leaf of mangrove, which has been fed to the sheep.